The need for community-controlled tools to monitor health impacts of housing and living conditions in Australia - Wyber, Rosemary; Summer, Kate; Stacey, Ingrid; Stiles, Samantha; Katzenellenbogen, Judith; Bowen, Asha C.; Burgess, Rachel (Frontiers in Public Health, 2025)
Despite millennia of strong and continuous culture, inadequate housing has profound consequences on the health and wellbeing of Aboriginal and Torres Strait Islander people in Australia. For example, the excessive and inequitable burden of childhood skin infections, rheumatic fever, gastrointestinal disease and ear infections can all be linked to failures in housing policy, funding and maintenance. Aboriginal and Torres Strait Islander communities and peak bodies continue to call for greater community control and investment in housing. A commonality among stakeholders in this otherwise complex and contested space is the association between poor housing and poor health, and the need to evaluate the health impacts of housing improvement initiatives which speak literally to this connection, e.g., Housing for Health [New South Wales (NSW), 1997-current], Fixing Houses for Better Health (National, 2005–2009), and Healthy Homes [Northern Territory (NT), 2021]. We explore the contemporary landscape of housing investments and initiatives seeking to improve health outcomes among Aboriginal and Torres Strait Islander people in Australia, as well as the dearth of quality evidence and agreed approaches to evaluation. We outline the need to develop a monitoring tool grounded in routinely collected primary care data which will provide community-controlled organizations with sovereign capacity to measure health outcomes associated with housing. This would in turn inform political accountability and scale-up of Indigenous housing initiatives that work.